1779 Vt. Acts & Resolves 59, An Act for Forming and Regulating the Militia; and for Encouragement of Military Skill, for the Better Defense of This State. - (:unkn) unknown (General Publisher, 1779)
That every listed soldier and other householder, shall always be provided with, and have in constant readiness, a well fixed firelock, the barrel not less than three feet and a half long, or other good firearms, to the satisfaction of the commissioned officers of the company to which he doth belong, or in the limits of which he dwells; a good sword, cutlass, tomahawk or bayonet; a worm, and priming wire, fit for each gun
--
Keywords: ARMED FORCES